Development of the child's personality as the basic value of home education - Liliia Kobylianska (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
Education in a post-industrial society serves a person as far as social and professional protection is concerned. It allows one to adapt to changes in life, to develop the mind and soul, or to reflect on the challenges of the new millennium. The humanistic values of education cause the change of the authoritarian-disciplinary model of tuition to the person-oriented one. It is important to turn knowledge into a personal value; to generate positive motivation; to deepen individualization in education. Education should be aimed at the development of the individual in all its diversity. The modern market of educational services in Ukraine is marked by diversity. Ukrainian education is trying to form a new generation of the national elite, reviving and introducing alternative models and forms of education by reforming the main links. Individual training and education among children occupies a special place. It is embodied in conditions of home (family) education. Home education is a phenomenon of the social sphere of society, the main characteristic of which is the individualization of the upbringing and education of children in the family, carried out by parents or a specially invited teacher. It demonstrates the tendency to social interaction, the social mechanism for the development of family and public education. Home education solves social problems in an individual form, meets the consolidated requests of the family, its educational choice, as well as the needs of society and the states. Home tutorship is an educational system that implements the values of education through the unity of education and upbringing; comfortable interaction of the teacher with the child; use of advanced pedagogical technologies. The pedagogical potential of tutorship is the ability to provide an individual trajectory of the child's educational and personal development. Modern pedagogy is largely determined by the moral and spiritual values of the teacher, tutor, mentor, his world outlook, views of the world, moral attitudes. In the conditions of home (family) education, home teachers, teachers, tutors perform a number of social functions (socialization, adaptation, socio-cultural rehabilitation, etc.), as well as traditional duties - to teach, to educate, to enlighten, to develop.